STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MTS ALMAARIF 03 SINGOSARI - Ainur Rohmah Saidah; Dian Mohammad Hakim; Arief Ardiansyah (VICRATINA, 2022)
The aims of this study are to: (1) Describe the strategies used by Islamic religious teachers to motivate students to learn. (2) Please explain the increase in student motivation in MT. Almar Riff 03 Shingosari. (3) State the obstacles and supporting factors to increase students' motivation to learn in MT. Almarif 03 Singosari. The results showed the success of Islamic religious teachers in motivating students to study at MT. Almaarif 03 Singosari is very good and growing. This can be seen from the students who initially had difficulty taking classes and leaving the class, but now they are getting better, study hard and read a lot. Students who usually come, sit, and leave. When they dare to ask questions and express their opinions during the learning process. And even now, it reflects the morale of the students, who always respect their teachers by shaking hands at every meeting. That is, students will be more motivated to learn not only in terms of numbers such as grade books but also in terms of social morals, which MT actually wants. Almaarif 03 Singosari Be a moral person because it is in accordance with the vision and mission of the school.